Xanthene dyes and amino acids containing thioether or mercaptan groups as potential components of free-radical polymerization photoinitiating compositions - Ścigalski, F.; Pączkowski, J. (Polimery, 2022)
Quenching of the triplet state in benzophenone and in xanthene dyes in the presence of amino acids obeys the mechanism of photoinduced intermolecular electron transfer (PET), which is followed by transformations producing free radicals able to initiate polyme- rization. Initiation systems were studied in free-radical polymerization of polyoxyethylene glycol diacrylate (PEGDA), based on xanthene dyes (Table 1) as primary light absorbing chromophores, which were used as initiators, and amino acids carrying a thioether or a mercaptan group as electron donors, which were used as co-initiators. PEGDA was polymerized in a (3:1 by vol.) mixture with 1% NH4OH, pH 11.8. The photo-redox pairs composed of a xanthene dye and a sulfur(II)-carrying amino acid were found to be effective initiators (Table 3, Fig. 1); the maximum polymerization yield was achieved with the amino acids of the methionine group, acting as electron donors, that were used in the composition with each dye examined. A scheme (III) is suggested to describe the fundamental photochemical processes occurring in the polymerization. The essential effect is emphasized, exercised by the subsequent processes occurring immediately after electron transfer, on the rate of the PET-photoinitiated polymerization of PEGDA. This is true particularly of decarboxylation of the cation-radical having the radical center located on the sulfur atom, leading to alpha-aminoalkyl radicals able to initiate polymerization.